OPTIMALISASI TATA KELOLA KEUANGAN DESA MELALUI PENDEKATAN PEMBANGUNAN ZONA INTEGRITAS DESA (ZiDes) DI DESA CIALAM JAYA KECAMATAN KONDA KABUPATEN KONAWE SELATAN - La Ode Anto; Fitriaman; Syamsir Nur; Ika Maya Sari; Waode Aswati (CV. ALIM'SPUBLISHING, 2023)
This study aims to analyze the effectiveness of the Village Integrity Zone Development Approach (ZiDes) in improving village financial governance in Cialam Jaya Village, Konda District, South Konawe Regency. The ZiDes approach is an effort to strengthen transparency, accountability and public participation in financial management. The research method uses surveys, interviews and document analysis to measure the impact of ZiDes implementation on village financial governance. The results of the study show that the ZiDes Approach has succeeded in increasing transparency in presenting village financial information. The village community and village officials are actively involved in the decision-making process related to the village budget